Jungle Beer: An entrepreneur’s journey - TULI, Kapil R. (Institutional Knowledge at Singapore Management University, 2013)
This case follows Aditya Challa, a craft beer aficionado, whose passion for good beer led him on an international quest to study the art of brewing in Scotland and eventually to Singapore, where he started a microbrewery business with his friends in 2011. By October 2012, sales of his craft beer had been increasing 20% per month, bringing up his production to about one-third operating capacity. However, future growth remained uncertain – with specific challenges pertaining to distribution and branding. Craft beer was still a relatively unknown concept in the city-state, and consumers remained sceptical of premium priced local beer. Moreover, big breweries in the Singapore market had already locked down most retailers with exclusive draft contracts. Challa reviewed his business model and growth strategy in terms of how and where he could sell his beer while continuing to build the Jungle Beer brand.